Use of Internet-Based Academic Information Systems Web in the Development of Quality of Education Administration - Marantika Marantika; Khojir Khojir; Siti Nor Asiah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to design a WEB-based AIS in quality development. Web-Based Academic Information System is a system that informs online student active reports and web-based education quality improvement to accelerate the quality of information delivery. The menu can only be accessed by students, teachers, and administrators. The research method uses a qualitative approach that describes research based on a philosophical explanation of postpositivism. In addition, this research method was chosen as a tool for conducting more profound observations of natural objects. The procedure for collecting data was obtained from the literature study by taking theory from supporting books and the internet as an additional reference and comparison for library research. Data analysis procedures by developing systems and designing or designing systems for presenting information. This research also requires hardware, software, user interface, input, and output. The results of a study in building this system using DFD tools, Context Diagrams, ERD, Flowcharts, and programming languages PHP, HTML, and MySQL as databases.